1997
DOI: 10.1103/physrevlett.78.1408
|View full text |Cite
|
Sign up to set email alerts
|

First-Order Transition in the Breakdown of Disordered Media

Abstract: We study the approach to global breakdown in disordered media driven by increasing external forces. We first analyze the problem by mean-field theory, showing that the failure process can be described as a first-order phase transition, similarly to the case of thermally activated fracture in homogeneous media. Then we quantitatively confirm the predictions of the mean-field theory using numerical simulations of discrete models. Widely distributed avalanches and the corresponding meanfield scaling are explained… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
227
1
3

Year Published

2000
2000
2018
2018

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 230 publications
(253 citation statements)
references
References 41 publications
(53 reference statements)
22
227
1
3
Order By: Relevance
“…This corresponds to the point S in Fig. 3 and as it was suggested by many authors [7,9,14] is in situ a spinodal point of the model. As the constant external stress σ approaches So, we have found that under the EBC of constant stress the FBM exhibits presence of the first order phase transition and spinodal.…”
Section: Equation Of State For the Constant Stress σ = Const As An Ebcmentioning
confidence: 99%
“…This corresponds to the point S in Fig. 3 and as it was suggested by many authors [7,9,14] is in situ a spinodal point of the model. As the constant external stress σ approaches So, we have found that under the EBC of constant stress the FBM exhibits presence of the first order phase transition and spinodal.…”
Section: Equation Of State For the Constant Stress σ = Const As An Ebcmentioning
confidence: 99%
“…In previous simulations the exponent resulted to be close to τ = 5/2 , the value expected in the fiber bundle model (FBM) [34,35]. In the FBM, load is redistributed equally in all the fibers, representing thus a sort of mean-field limit of the RFM [32]. The load transfer in the RFM is long-ranged and is thus possible that RFM and FBM display universal behavior [36].…”
Section: Introductionmentioning
confidence: 99%
“…The qualitative behavior of the avalanche statistics is well understood in FBM, which can be solved exactly representing a mean-field version of the RFM [32]. The FBM can be formulated as a parallel set of fuses, with random breaking threshold, under a constant applied current I.…”
Section: Avalanchesmentioning
confidence: 99%
See 1 more Smart Citation
“…One central property of first-order phase transitions is the presence of a macroscopic instability (discontinuity ofthe order parameter) atthe transitionpoint. This framework was thus proposed to describe the global breakdown of a system in fracturing phenomena [Andersen et al, 1997;Zapperi et al, 1997a]. However, dislocation-driven viscoplastic deformation during viscoplastic steady state behavior does not lead to a breakdown (ormacroscopic instability) of the system.…”
Section: Discussionmentioning
confidence: 99%